2023
DOI: 10.1038/s41467-023-39267-x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of potent pan-variant SARS-CoV-2 neutralizing antibodies from individuals with Omicron breakthrough infection

Abstract: The SARS-CoV-2 Omicron variant evades most currently approved neutralizing antibodies (nAbs) and caused drastic decrease of plasma neutralizing activity elicited by vaccination or prior infection, urging the need for the development of pan-variant antivirals. Breakthrough infection induces a hybrid immunological response with potentially broad, potent and durable protection against variants, therefore, convalescent plasma from breakthrough infection may provide a broadened repertoire for identifying elite nAbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The cellular antiviral activity of GZNL-P36 was examined by a cell protection assay. In this assay, the cytopathic effect (CPE) of SARS-CoV- 2-infected Vero E6 cells with or without treatment by the compounds was assessed using Celigo Image Cytometer 39 . The cells were challenged with WT SARS-CoV-2 and two other variants Omicron BA.5 and XBB.1.…”
Section: Resultsmentioning
confidence: 99%
“…The cellular antiviral activity of GZNL-P36 was examined by a cell protection assay. In this assay, the cytopathic effect (CPE) of SARS-CoV- 2-infected Vero E6 cells with or without treatment by the compounds was assessed using Celigo Image Cytometer 39 . The cells were challenged with WT SARS-CoV-2 and two other variants Omicron BA.5 and XBB.1.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we observed more somatic mutations in IGHV3-53 mAbs isolated from breakthrough infection donors than those isolated from ancestral SARS-CoV-2 infection. Recently, several studies showed that the affinity maturated IGHV3-53 mAbs, such as P5S-2B10 (from WT convalescents) [ 56 ], 10-5B (from inactivated vaccinees) [ 57 ], and TH132 (from BA.1 breakthrough infected donors) [ 58 ], are able to protect K18-hACE2 mice from the challenge of Omicron BA.1, BA.2, and BA.5, respectively. Collectively, our analysis provides a holistic view of the kinetics of the spike-specific antibody response and identifies which of them is induced by ancestral SARS-CoV-2 infection or vaccination that will create long-term or/and cross-reactive B-cell memory.…”
Section: Discussionmentioning
confidence: 99%
“…Although the decision process for clinical development would likely be delayed initially, as input data may not be available, the inclusion of in silico generated data, next to classic neutralization potency, affinity, and developability, may result in longer lasting clinical efficacy. Another strategy against viral escape by new strains is to develop pan-variant reactive antibodies, although their mode of action is not necessarily neutralization [ 43 ], or several infections or vaccinations of an individual are needed to develop such an immune response [ 44 , 45 ] or the epitopes to target. Nevertheless, in an urgent pandemic setting, the question remains if such strategies would be economically viable compared to the obvious strategy of isolating neutralizing antibodies from survivors of the initial pandemic phase.…”
Section: Discussionmentioning
confidence: 99%